Prevalence of sexually transmitted infections in female clinic attendees in Honiara, Solomon Islands. Issue 4 (28th April 2015) - Marks, M; Kako, H; Butcher, R; Lauri, B; Puiahi, E; Pitakaka, R; Sokana, O; Kilua, G; Roth, A; Solomon, A W; Mabey, D C
Abstract : Objectives: This study sought to determine the prevalence of common bacterial sexually transmitted infections, including Chlamydia trachomatis and Neisseria gonorrhoeae, in women attending clinics in the Solomon Islands. Methods: We conducted a sexual health survey among women attending three nurse-led community outpatient clinics in August 2014, to establish the prevalence of bacterial sexually transmitted infections in female clinic attenders in Honiara, Solomon Islands. Vaginal swab samples were tested for infection with C. trachomatis and N. gonorrhoeae using a commercial strand displacement amplification assay. Serum samples were tested for syphilis. Results: We enrolled 296 women, aged 16–49, attending three clinics. Knowledge of safe sexual practices was high but reported condom usage was low. The prevalence of infection with C. trachomatis was 20%. The prevalence of infection with N. gonorrhoeae and syphilis were 5.1% and 4.1%, respectively. Conclusions: Bacterial sexually transmitted infections are a major health problem in the Solomon Islands. Interventions are urgently needed.